Exposure to Second-hand Smoke While Breastfeeding Cause a Reducing Its Protective Properties and Higher Diarrhea Prevalence on Infants - Wahyutri, Endah; Saadah, Nurlailis; Kalsum, Umi; Purwanto, Edi; Setiadi, Rizky; Ratnawati, Dan (International Journal of Psychosocial Rehabilitation, 2020)
Diarrhea is the second leading cause of mortality among children younger than age 2 years in Indonesia after upper respiratory infections. The scope of mothers who reported exclusive breastfeeding in East Kalimantan is 29% and the prevalence of smoking father is 25%, so there is higher percentage of mothers and children exposed to second-hand smoke. We identify and diagnose 170 children Breastfeeding pattern as the independent variable, occurrence of Diarrhea as the dependent variable, and intermediate variables including children's age and smoking father. The statistical analyses used multiple logistic regression. There are 31.2% children with 1-12 months of age with Diarrhea, 37.6% of them being fed breast milk exclusively, 59.4% partially, and 2.9% predominantly. Among them, 60.1% of fathers are actively smoking. We found association between smoking father and the occurrence of Diarrhea on children with logistic regression analysis p value 0.030 and Exp.(B) value of 2.077 (95% CI: 1.072-4.025). Logistic regression analysis presents the evidence of association between breastfeeding pattern and Diarrhea. The association of partial and exclusive breastfeeding and Diarrhea occurrence with p value of 0.0018 and 0.005 each. Exp.(B) value of 3.0 (95% CI: 1.4–6.5). Exclusive breastfeeding could help preventing of Diarrhea. Smoking father would affect the protective properties of breast milk with cigarette smoke exposure risk higher prevalence of Diarrhea.